Labor in Israel : beyond nationalism and neoliberalism - Preminger, Jonathan, 1975- (ILR Press, an imprint of Cornell University Press, 2018)
Using a comprehensive analysis of the wave of organizing that swept the country starting in 2007, Labor in Israel investigates the changing political status of organized labor in the context of changes to Israel's political economy, including ...